Stratégies politiques des indigènes dans l’Amazonie brésilienne : agence, échelle et territoire - João Pacheco de Oliveira (Cahiers des Amériques Latines)
The purpose of this article is to identify some basic organizational principles of the contemporary political world of indigenous movements in the Brazilian Amazon. To understand strategies and categories of language required in these new scenarios we must use as tools of investigation the notions of agency, scale and territorialization (it means the process of making a legal and political relationship between people and territory). Aboriginal communities, still subject to the tutelary practices of Brazilian society and the guardianship of national state, are fighting for juridical and administrative recognition of ethnic territories, which represents the starting point for his political and economic projects as well as access to civil rights and citizenship.